Ultrasound-guided percutaneous cryoneurolysis for management of acute sternal fracture pain. (February 2023) - Kwater, A.P.; Sen, S.; de Haan, J.B.; Ge, M.A.; Kim, A.M.; Hernandez, N.
Abstract: Background: Establishing adequate analgesia for rib and sternal fractures remains a challenge due to the prolonged nature of the associated pain. Historically, cryoneurolysis has demonstrated beneficial in treating chronic pain, and the recent development of hand-held devices has allowed its functionality to expand into the management of acute pain. Case: We present a polytrauma patient with sternal and multiple rib fractures that underwent ultrasound-guided intercostal cryoneurolysis at bedside, resulting in significant analgesia lasting several weeks and improving mobilization. This is the first report of the utilization of cryoneurolysis to treat acute sternal fracture pain. Conclusion: The most common sternal fracture pattern is transverse which only requires treatment of four intercostal nerves, making cryoneurolysis feasible in trauma centers. This portable, minimally invasive, and low risk technique has the added benefits of reducing opioid requirements, decreasing length of hospital stay, and improving mobility in polytrauma patients.